Circulating miRNAs as potential non-invasive biomarkers for ANCA-associated glomerulonephritis - Bošnjak, Matic; Večerić-Haler, Željka; Pipan Tkalec, Živa; Tomšič, Jakob; Boštjančič, Emanuela; Kojc, Nika (Frontiers in Immunology, 2025)
IntroductionAnti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is characterized by necrotizing small vessel vasculitis that frequently manifests as glomerulonephritis (AAV-GN). An accurate noninvasive biomarker reflecting active AAV-GN remains elusive. The knowledge of microRNAs (miRNAs), which have been considered as disease-specific biomarkers, is scarce and lacks validated data in AAV.MethodsThis study validated a renal tissue expression profile of candidate miRNAs specific to AAV-GN selected through prior screening using independent cohorts. The analysis was extended to serum samples to explore the potential of a circulating miRNA panel as a noninvasive biomarker for active AAV-GN. To substantiate the findings, we correlated the molecular data with clinical and histologic markers of AAV-GN activity.ResultsWe identified miR-21-3p, miR-181a-5p, and miR-181d-5p as potential biomarkers distinguishing AAV-GN from non-AAV renal diseases and healthy controls. In addition, miR-21-3p and miR-181d-5p correlated with the presence of active AAV-GN, while miR-181a-5p differentiated AAV-GN subtypes based on ANCA antigen specificity. ROC curve analysis demonstrated that the combined serum expression of miR-21-3p and miR-181a-5p reliably distinguished AAV-GN from other renal pathologies, including ANCA-positive cases without histologic evidence of AAV-GN.ConclusionOur findings highlight the potential of circulating miRNA expression signature as a noninvasive biomarker for ongoing AAV-GN in the appropriate setting. Larger confirmatory studies are essential to support the clinical application of miRNA-based biomarkers in AAV-GN diagnostics and disease monitoring.